2017
DOI: 10.1002/anie.201611320
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the Intrinsic Nature of Electronic Transitions from Gas‐Phase Spectroscopy of Molecular Ion/Zwitterion Complexes

Abstract: A molecule's color is governed by the nature of its electronic transitions. Herein we show that the degree of charge transfer can be assessed by measuring the change in absorption induced by complexation with the betaine zwitterion. Our approach benefits from direct formation of complexes by electrospray of a mixture solution, followed by photodissociation action spectroscopy. We explored two ion groups: 1) No permanent dipole moment due to even charge delocalization (e.g. MnO ) and 2) Non-even charge distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…The absorption by the 2 + B complex has a maxiumum at 460 nm, and is shifted by approximately 0.6 eV as compared with the bare chromophore. This is an anomalously large blue shift, being a factor of two larger than the largest blue shift due to betaine complexation measured so far [27,28]. The absorption band of the 1 + B complex is considerably wider and peaked at 410 nm.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…The absorption by the 2 + B complex has a maxiumum at 460 nm, and is shifted by approximately 0.6 eV as compared with the bare chromophore. This is an anomalously large blue shift, being a factor of two larger than the largest blue shift due to betaine complexation measured so far [27,28]. The absorption band of the 1 + B complex is considerably wider and peaked at 410 nm.…”
Section: Resultsmentioning
confidence: 59%
“…more than six times larger than that of water. It has recently been shown that electrospraying a solution containing the chromophore of choice and betaine results in the production of mixed complexes [27,28]. The structure of these complexes is expected to be one where the negative part of the betaine is located close to the positive charge in the chromophore, inducing a strong local electric field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain the intrinsic properties, the molecule has to be studied isolated in the gas phase. After the absorption spectrum of the bare Chl is established, perturbations can be included by complexation of the pigment with various adducts to study the effect of individual interactions …”
Section: Figurementioning
confidence: 99%